Powstanie i rozwój instytucjonalnych form ochrony interesów konsumenta w Polsce Ludowej - Piasna, Barbara (Wydział Prawa i Administracji UAM, 1971)
Protection of the consumer's interests is needed also in the socialistic system as a consequence of commodity production under the conditions of socialistic economy. However, the main cause of prejudicing the consumer's interests in the producer and seller's market, particularly in the initial phase of constructing the foundations of socialism. In those conditions the consumer may be exposed to a financial loss and in particular to a disadventageous spending of his pecuniary means. He may be forced by the circumstances to buy commodities that meet his requirements either incompletely or in the wrong way. On the other hand the condition of the producer and seller's market are favourable to speculations, frauds of various kind and other law-breaking activities. For that reason the state constitutes supervising bodies and improves means and methods of securing the consumer's interests. For that purpose also commissions for preventing speculations and malpractice, institutions for supervising quality, the State Inspection of Commerce and other institutions are brought into existence. The state issues a number of legal regulations in order to protect material interests of the consumer. Special campaigns and actions in this field are encouraged by the state and taken by trade-unions and various social organizations. In consequence the system of institutional forms for protecting the consumer in Poland preserves him from purchasing low quality goods more and more effectively, protects him against facts of speculation, creates easier and improved terms of purchase and brings about anticipation of his requierements.
Institutional Forms Protecting the Consumer's Interests in the Polish People's Republic